2015
DOI: 10.1155/2015/510810
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Microarrays Identify Blood Group Precursor Cryptic Epitopes as Potential Immunological Targets of Breast Cancer

Abstract: Using carbohydrate microarrays, we explored potential natural ligands of antitumor monoclonal antibody HAE3. This antibody was raised against a murine mammary tumor antigen but was found to cross-react with a number of human epithelial tumors in tissues. Our carbohydrate microarray analysis reveals that HAE3 is specific for an O-glycan cryptic epitope that is normally hidden in the cores of blood group substances. Using HAE3 to screen tumor cell surface markers by flow cytometry, we found that the HAE3 glycoep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Results of the microarray assay are shown as microarray scores, i.e., means of the log2-transformed fluorescent intensities (MFIs) of multiple detections of a given antigen preparation (Figure 1A and Supplementary Table 1). Glycan-specific ELISA was performed as described in Figure 1 legend following our standard protocol (20). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Results of the microarray assay are shown as microarray scores, i.e., means of the log2-transformed fluorescent intensities (MFIs) of multiple detections of a given antigen preparation (Figure 1A and Supplementary Table 1). Glycan-specific ELISA was performed as described in Figure 1 legend following our standard protocol (20). …”
Section: Methodsmentioning
confidence: 99%
“…This antibody was raised by a murine mammary tumor antigen epiglycanin (EPGN) (21) but was found to cross-react with a number of human epithelial tumors in tissues including the lung, prostate, bladder, esophagus, and ovaries (2224). In a recent flow-cytometry-based screening for tumor cell surface biomarkers, we found that HAE3 also strongly cross-reacts with human breast tumors (20). …”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…This microarray finding was further validated by glycan-specific enzyme-linked immunosorbent assay (ELISA) and glyco-conjugate-based epitope competition assays [13,14]. Figure 2 is a schematic of the blood group substance structure with the common blood group precursor core structure highlighted.…”
mentioning
confidence: 93%